THE IMPACT OF CREDIT RISK ON THE PROFITABILITY WITH CHARACTERISTICS BANK AS CONTROL VARIABLES - Fauziah, Rini Syahril; Fadhilah, Nur Hidayah K (Universitas Tidar, 2021)
The purpose of this study is to determine the extent of the influence of bad loans on return on assets with the characteristics of the bank as a controller in the banks listed on the Indonesia Stock Exchange in 2015-2019. Purposive sampling was chosen as a sampling technique where the data obtained were 23 companies with a 5-year observation period. Multiple linear regression analysis was used to analyze the data. The results found from this study simultaneously bad credit influences return on assets. Partially, net performing loans have a negative and significant effect on return on assets. Then, the Loan to Deposit Ratio also has a positive and significant effect on return on assets. The existence of the characteristics of the bank as a controller in this study influences the relationship between the independent variable and the dependent variable in this study.